Conceptualising Communication Media And Farmer's Reaction In Problem Solving - Bin Ismail I.; Rosidayu Sabran; Mohd Yahya Mohamed Ariffin (Gyandhara International Academic Publications, 2024)
Indexed by SCOPUS